English spelling among the top priorities in pronunciation teaching: Polglish local versus global(ised) errors in the production and perception of words commonly mispronounced - Nowacka, Marta (Research in Language, 2016)
This paper presents the results of a questionnaire and recording-based study on production and recognition of a sample of 60 items from Sobkowiak’s (1996:294) ‘words commonly mispronounced’ by 143 first-year BA students majoring in English. 30 lexical items in each task represent 27 categories defined by Porzuczek (2015), each referring to one aspect of English phonotactics and/or spelling-phonology relations. Our aim is to provide evidence for the occurrence of local and globalised errors in Polglish speech. This experiment is intended to examine what types of errors, that is, seriously deformed words, whether avoidable, ‘either-or’ or unavoidable ones, as classified in Porzuczek (2015), are the most frequent in production and recognition of words. Our goal is to check what patterns concerning letter-to-sound relations, are not respected in the subjects’ production and recognition of an individual word and what rules should be explicitly discussed and practised in a phonetics course. The results of the study confirm the necessity for explicit instruction on the regularity rather than irregularity of English spelling in order to eradicate globalised and ‘either-or’ pronunciation errors in the speech of students. The avoidable globalised errors which have turned out to be the most numerous in a production task include such areas of English phonotactics as: the letters <-old> and <oll>, ‘mute consonant letters’, ‘isolated errors’ and two categories related to the reduction of unstressed syllables: ‘reduce the vowel in stress-adjacent syllables and in syllables following the stressed one to /ə/ or /ɪ/’ and ‘reduce <-ous>, <-age>, and <-ate> in nouns and adjectives.’ The hope is also expressed that once introducing spelling-to-sound relations becomes a routine procedure in pronunciation training, the strain on part of the students of memorizing a list of true local errors, phonetically challenging pronunciation exceptions, will be reduced to the absolute minimum.